Ketamine-Induced Cystitis: A Comprehensive Review of the Urologic Effects of This Psychoactive Drug - Danyon J. Anderson; Jessica Zhou; David Cao; Matthew McDonald; Maya Guenther; Jamal Hasoon; Omar Viswanath; Alan D. Kaye; Ivan Urits (Health Psychology Research)
Ketamine is a common medical anesthetic and analgesic but is becoming more widely used as a recreational drug. Significant side effects on the urinary tract are associated with frequent recreational ketamine use most notably ketamine-induced cystitis (KIC). Regular ketamine consumption has been shown to increase the risk of cystitis symptoms by 3- to 4-fold, and cessation of ketamine use is usually associated with improvement of symptoms. Common KIC-related problems are urinary pain and discomfort, bladder epithelial barrier damage, reduced bladder storage and increased pressure, ureter stenosis, and kidney failure, all of which significantly impact patients' quality of life. Furthermore, it becomes a vicious cycle when KIC patients attempt to manage their urinary pain with increased ketamine use. The precise pathophysiology of KIC is still unknown but several theories exist, most of which highlight the inflammatory signaling pathways leading to bladder epithelium damage due to presence of ketamine in the urine. Empirical treatment options for KIC are available and consist of ketamine cessation, noninvasive therapies, and surgery, and should be decided upon based on the time course and severity of the disease. Of note, cessation of use is strongly recommended for all KIC patients, and should be supplemented with motivational interviews and psychological and social support. It is crucial for clinicians to be familiar with KIC diagnosis and treatment, and to be prepared to have informed discussions with ketamine-using patients about the potential health consequences of ketamine.